Numerical study of the spin‐up of a tropical low over land during the Australian monsoon. (18th May 2016) - Tang, Shengming; Smith, Roger K.; Montgomery, Michael T.; Gu, Ming
Abstract : An analysis of numerical simulations of tropical low intensification over land is presented. The simulations are carried out using the MM5 mesoscale model with initial and boundary conditions provided by ECMWF analyses. Seven simulations are discussed: a control simulation, five sensitivity simulations in which the initial moisture availability is varied, and one simulation in which the coupling between moisture availability is suppressed. Changing the initial moisture availability adds a stochastic element to the development of deep convection. The results are interpreted in terms of the classical axisymmetric paradigm for tropical cyclone intensification with recent modifications. Spin‐up over land is favoured by the development of deep convection near the centre of the low circulation. As for tropical cyclones over sea, this convection leads to an overturning circulation that draws absolute angular momentum surfaces inwards in the lower troposphere leading to spin‐up of the tangential winds above the boundary layer. The intensification takes place within a moist monsoonal environment, which appears to be sufficient to support sporadic deep convection. A moisture budget for two mesoscale columns of air encompassing the storm shows that the horizontal import of moisture is roughly equal to the moisture lost by precipitation. Overall, surface moisture fluxes make a small quantitative contribution to the budget although, near the circulation centre, these fluxes appear to play an important role in generating local conditional instability. Suppressing the effect of rainfall on the moisture availability has little effect on the evolution of the low, presumably because, at any one time, deep convection is not sufficiently widespread.